Direct visualization of electrical transport-induced alloy formation and composition changes in filled carbon nanotubes by in situ scanning transmission electron microscopy - Aslam, Z; Lozano, J; Nicholls, R; Koos, A; Dillon, F; Sarahan, M; Nellist, P; Grobert, N (Elsevier, 2017)
In order to evaluate the applicability of metal-filled carbon nanotubes, it is crucial to understand their behaviour in the presence of electric currents. In this work we exploit the significant advantages of combining in situ experiments with scanning transmission electron microscopy in annular dark-field mode and related analytical techniques to gain further insights into the electrical transport induced transformations in Fe-filled P,N-doped multi-wall carbon nanotubes. With these synergistic analysis techniques, we could monitor in real time the dynamical effects that take place in the carbon nanotubes and their Fe filling as a consequence of the passing of an electric current and subsequent Joule heating. A detailed analysis of the formation, evolution and composition of intermediate phases has been possible employing in situ experiments with transmission electron microscopy, scanning-transmission electron microscopy and analysis techniques. We show that a multistage process occurs in which the Fe filling reacts with nitrogen to form an intermediate alloy phase, which then decomposes. The presence of high concentrations of nitrogen within the inner channel of the tube is found to be crucial to this process.